Efficacy of Transcranial Direct Current Stimulation Combined with Cognitive Training in the Treatment of Apathy in Patients with Alzheimer's Disease: Study Protocol for a Randomized Trial - Nguyen, Jean-Paul; Boutoleau-Bretonniere, Claire; Lefaucheur, Jean-Pascal; Suarez, Alcira; Gaillard, Helene; Chapelet, Guillaume; Abad, Sebastien; Van Langhenhove, Aurelien; Nizard, Julian; de Decker, Laure (Reviews on Recent Clinical Trials, 2018)
Background: Apathy, commonly defined as the loss of motivation, is a symptom frequently encountered in Alzheimer's Disease (AD). The treatment of apathy remains challenging in the absence of any truly effective medications. Transcranial Magnetic Stimulation (rTMS) or Transcranial Direct Current Stimulation (tDCS) can improve cognitive disorders, but do not appear to improve apathy. Isolated cognitive training also appears to have no effect on apathy. We propose to test the efficacy of a new procedure for the treatment of apathy in AD patients consisting of a combination of tDCS and cognitive training, based on the latest guidelines for the design of therapeutic trials in this field. Methods/Design: This article primarily describes the design of a monocentre, randomized, doubleblind trial to be conducted in France to evaluate the effect of the combination of tDCS and cognitive training on apathy compared to a group treated exclusively by cognitive training (sham tDCS). Twenty- four patients under the age of 90 years with mild-to-moderate Alzheimer's disease (Mini Mental State Examination score between 15 and 26/30) (MMSE)) presenting clinically significant apathy evaluated by the Apathy Inventory (AI) and the NeuroPsychiatric Inventory (NPI) apathy subscore will be enrolled. Severe depression will be excluded by using the NPI depression subscore. Treatment will comprise 10 sessions (D0-D11) including tDCS (bilateral prefrontal, temporal and parietal targets) and Cognitive Training (Cog) (6 simple tasks involving working memory, language and visuospatial function). After randomization (ratio 2:1), 16 patients will receive the complete treatment comprising tDCS and Cog (group 1) and 8 patients will be treated exclusively by Cog (sham tDCS) (group 2). The primary endpoint will be a significant improvement of the AI score by comparing baseline measures (D-15) to those recorded one month after stopping treatment (D44). Secondary endpoints will be an improvement of this score immediately after treatment (D14), 2 weeks (D29) and 2 months (D74) after stopping treatment and improvement of the MMSE score, NPI apathy subscore, ADAS Cog (Alzheimer Disease Assessment cognitive Scale subsection), ADCS-ADL (Alzheimer Disease Cooperative Study-Activities of Daily Living), FAB (Frontal Assessment Battery) and the latency of P300 evoked potentials at the same timepoints. Conclusion: The purpose of our study is to check the assumption of tDCS and cognitive training efficacy in the treatment of apathy encountered in AD patients and we will discuss its effect over time.
Keywords: treatment